PERSEPSI JAMAAH MASJID DI KECAMATAN TELUK SEGARA DAN GADING CEMPAKA TERHADAP KOMUNITAS SAFARI SUBUH MINANG DALAM MELESTARIKAN GERAKAN SUBUH BERJAMAAH DI KOTA BENGKULU - Muhammad Amin Akbar; Miswanti; Rasman (JOISCOM (Journal of Islamic Communication), 2024)
This research aims to analyze the perceptions of mosque congregations in Teluk Segara District and Gading Cempaka District toward the Minang Subuh Safari Community in preserving the congregational Fajr prayer movement in Bengkulu City, using Schmitt's sociological theory. The research method used is qualitative with a phenomenological approach. Data collection techniques were carried out through participant observation and in-depth interviews. The results show that mosque congregations in Teluk Segara District and Gading Cempaka District have a positive perception of the Minang Subuh Safari Community. This community is considered a catalyst for the revival of the congregational Fajr prayer movement in Bengkulu City. Based on Schmitt's sociological theory, the positive perception of mosque congregations toward the Minang Subuh Safari community is based on several factors, namely: Social factors: Minang residents tend to be more active because they value interaction and community relationships. However, local congregations have varying levels of participation depending on the location of the mosque. Economic factors: Many congregants are still focused on economic activities, making them less enthusiastic about this activity. Religious factors: The low level of religious understanding makes some congregants less aware of the importance of this activity. The perception of mosque congregations toward the Minang Subuh Safari community, which has contributed to preserving the congregational Fajr prayer movement in Bengkulu City, is positive and favorable. This is evidenced by the view of congregants who actively participate in organizing congregational Fajr prayers. However, even after this activity is held, many congregants still have not experienced a significant change in their participation in Fajr prayers at the mosque. Keywords: Perception, Mosque Congregation, Minang Subuh Safari Community, Congregational Fajr Prayer Movement, Bengkulu City